Antimicrobial Activity of Remineralizing Ion-Doped Amorphous Calcium Phosphates for Preventive Dentistry - Degli Esposti, Lorenzo; Ionescu, Andrei C.; Carella, Francesca; Adamiano, Alessio; Brambilla, Eugenio; Iafisco, Michele (Frontiers in Materials, 2022)
We have synthesized citrate-stabilized amorphous calcium phosphates doped with fluoride (F-ACP), strontium (Sr-ACP), and zinc (Zn-ACP) ions. ACP based materials were proven to have excellent remineralizing action on demineralized dental hard tissues while F-, Sr2+, and Zn2+ ions are known to have antimicrobial activity, so the aim of our work was to produce multipurpose materials for preventive dentistry that inhibit cariogenic bacteria and remineralize dental enamel and dentin. Doping ions were successfully incorporated into ACP up to 2 wt.% F- and 12 wt.% Sr2+ or Zn2+ without altering ACP physical-chemical properties. Evaluation of viability of Streptococcus Mutans biofilm treated with ion-doped ACP materials showed that F-ACP and Sr-ACP have a direct inhibitory effect while Zn-ACP has a negligible effect. The different antibacterial activity was correlated to the ion-release properties of the materials, as in conditions mimicking a cariogenic environment F-ACP and Sr-ACP have a release of ca. 5-7 % of total F- or Sr2+ while only ca. 1 % of total Zn2+ is released. All ion-doped ACP materials are able to remineralize in vitro demineralized human enamel slabs by epitaxial deposition of a new ion-doped crystalline phase in direct contact with the pristine one. Enamel slabs remineralized with F-ACP has an antibacterial/bacteriostatic action, proving that F-ACP acts as preventive antimicrobial agent. Overall, our work demonstrates the high potential of ACP doped with antibacterial ions for the preventive treatment of dental caries.